2019
DOI: 10.31235/osf.io/962yu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Capital Accountability and Construct: Evidence from Islamic Microfinance Institutions in Malaysia

Abstract: To identify the human capital construct that significantly relates to the performance of Islamic organizations, this study obtained data from Islamic microfinance organizations in Malaysia using the survey questionnaire method. In addition, we interviewed renowned scholars in the fields of Islamic accounting and Shariah law. Consequently, this study proposes an extended model of human capital that is applicable to Islamic organizations. Apart from knowledge and competency, this study includes spiritual value a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The RBV concept is consistent with a study conducted by Kamaluddin et al (2016), which showed that small and medium-sized firms (SMEs) should use all available assets to gain a competitive edge and improve performance. This argues that SMEs must recognise and capitalise on their particular resources and competencies in order to obtain a competitive advantage and achieve long-term success.…”
Section: Literature Review 21 Theoretical Review 211 Resource-based V...supporting
confidence: 77%
“…The RBV concept is consistent with a study conducted by Kamaluddin et al (2016), which showed that small and medium-sized firms (SMEs) should use all available assets to gain a competitive edge and improve performance. This argues that SMEs must recognise and capitalise on their particular resources and competencies in order to obtain a competitive advantage and achieve long-term success.…”
Section: Literature Review 21 Theoretical Review 211 Resource-based V...supporting
confidence: 77%
“…Many researchers have called for the inclusion of other concepts and determinants of the components of IC, which provides a more comprehensive and clearer picture of the human and social aspect in organisations. Kamaluddin et al (2019) conducted a study to identify the HC constructs related to the performance of Islamic microfinance organisations in Malaysia using a mixed methodology. Based on interviews with scholars and experts, they proposed an extended model of HC that is relevant to Islamic organisations.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Aydin (2015) states that the Islamic understanding and wisdom about the environment is more sustainable, very demanding of its adherents and profoundly important both theoretically and practically in comparison to conventional social business platforms. According to Ahmed et al (2015) and Kamaluddin et al (2018), the truly Islamic way of life improves social sustainability and makes possible a fully realized and comprehensive human and societal development. In Islam, infrastructure development must incorporate a sustainable agenda (Ahmed et al 2015).…”
Section: Conventional and Islamic Theories And Views Of Sustainable D...mentioning
confidence: 99%
“…Islam encourages an accommodative sustainable business model in which people can thrive and enjoy the fruits of economic development (Alam et al 2013(Alam et al , 2015(Alam et al , 2017a(Alam et al , 2018. Gamieldien (2010) and Kamaluddin et al (2018) mentions that in order to live a healthy and progressive life within an Islamic framework, human beings need to understand the very concept of sustainability. Further to the discussion above, Islam is actually far ahead in terms of the discussion highlighted decades ago by the Brundtland Report on United Nations sustainable development in 1987 (Aris et al 2018).…”
Section: Conventional and Islamic Theories And Views Of Sustainable D...mentioning
confidence: 99%